Optimization of process variables in drilling of LM6/fly ash composites using Grey-Taguchi method. (2022) - Sarala Rubi, C.; Udaya Prakash, J.; Rajkumar, C.; Mohan, A.; Muthukumarasamy, S.
Abstract: Drilling is a critical step in the hole-making operation. It is quite beneficial for part assembly. Hard particulates introduced into the continuous phase of the composite materials, makes them hard to process. As a result, optimizing the drilling variables is inevitable . The primary goal of this study is to manufacture LM6/Fly Ash with weight percentages of fly ash 3, 6 and 9 adopting the stir casting technique. The second objective is to use Taguchi's Design of Experiments (L27 OA) to drill composite materials using feed rate (F), spindle speed (S), drill material (D), and % of reinforcement (R) as drilling process variables at 3 levels. The ultimate goal is to optimize the drilling process variables for obtaining minimum thrust force (TF), surface roughness (SR) and burr height (BH) using multi-objective Grey Relational Analysis. The optimum process variable achieved is F1 S3 D3 R3, i.e., 50 mm/min, 3000 rpm, TiN-coated drill bit and 9 wt% of fly ash.